The Use of Frozen Theme Strategic Intervention Material to Improve the Uniformly Accelerated Motion Proficiency of Grade 9 Students - Pantilon, Lasheundra Nie D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study aimed to determine the used of Frozen Theme Strategic Intervention Material in improving the uniformly accelerated motion (UAM) proficiency of grade nine students at Jesus F. Magsaysay Technical Vocational High School. The study used quasi-experimental research method which involved fourthy five students in the control group and fourthy five in the experimental group. The control group was taught using the traditional method of instruction (TMI) while the experimental group was taught using the Frozen Theme Strategic Intervention Material (FT-SIM). A fifty-item conceptual test and the UAM Learning Strategies questionnaire were the tools used in the study. The study revealed that a typical Grade nine student is aged fourteen and male. Prior to the treatment, the Grade nine students in both the control and experimental groups were performing Fairly Satisfactory in terms of level of proficiency. After the treatment, the students’ proficiency on UAM in the experimental group had improved to Very Satisfactory while the control group remained to be in the Fairly Satisfactory level. There is a significant difference in the level of proficiency of science students in the experimental group and no significant difference was noted in the control group. Both the control and experimental groups rarely practice the learning strategies in the uniformly accelerated motion (UAM), hence, the strategic intervention material was developed. The content teachers evaluated the instructional material as very useful.